Crop productivity, soil fertility and economics of soybean (Glycine max), chickpea (Cicer arietinum) and blond psyllium (Plantago ovata) under organic nutrient management practices - RAMESH, P; PANWAR, N R; SINGH, A B (The Indian Journal of Agricultural Sciences, 2010)
A field experiment was conducted during rainy (kharif) and winter (rabi) seasons of 2004–08 to study the effect of different combination of organic manures involving cowdung manure, poultry manure and vermicompost vis-à-vis recommended doses of fertilizers and control on the yield potential, soil fertility and economics of soybean [Glycine max (L.) Merr.], chickpea (Cicer arietinum L.) and blond psyllium or isabgol (Plantago ovata Forsk) in deep Vertisols of central India. The mean of 4-year data indicated that the highest soybean seed yield (1 069 kg/ha) was obtained with the application of cowdung manure 4 tonnes/ha and for chickpea, a combination of cowdung manure 2 tonnes/ha + vermicompost 1.5 tonnes/ha resulted in the highest seed yield (1 766 kg/ha) which was at par with the yield obtained by the recommended dose of fertilizers (1 693 kg/ha). Isabgol seed yield was the highest (1 291 kg/ha) with the combined application of cowdung manure 1 tonne/ha + vermicompost 0.7 tonne/ha + poultry manure 0.5 tonne/ha, which was superior to the yields obtained with the recommended dose of fertilizers (1 153 kg/ha). The seed quality of these crops was at par with the treatments receiving either organic manures or chemical fertilizers but was significantly superior to the control. At the end of the fourth cropping cycle, combined application of cowdung manure + vermicompost + poultry manure resulted in the improvement of soil organic carbon content, available soil N, P and K compared to either recommended dose of fertilizers or control. Soybean–chickpea recorded the highest gross returns (` 43 927), net returns (` 23 890) and benefit : cost ratio (2.19) compared to the soybean–isabgol cropping system. Combined application of cowdung manure + vermicompost + poultry manure resulted in the highest gross returns (` 45 008), net returns (` 24 786) and benefit : cost ratio (2.22) compared to either chemical fertilizers or the control.